Penggunaan Silica Fume Sebagai Pengganti Sebagian Semen Dengan Penambahan Bubur Kertas Dan Superplasticizer Terhadap Kuat Tekan Dan Kuat Lentur Beton - Pala'langan, Wiseldes; Sariman, Syahrul; Mulyani, Savitri Prasandi (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Indonesia is a developing country with rapid progress in infrastructure and technology. Cement production requires a significant amount of energy and generates considerable waste. Innovation is essential to create construction materials that are cost-effective, energy-efficient in production, and produce minimal carbon dioxide and other hazardous waste. The use of silica fume as a partial replacement for cement, combined with paper pulp and superplasticizer in concrete mixtures, is expected to enhance concrete strength. This approach may also help reduce environmental pollution from cement production. In this study, 10% of the cement in each sample was substituted with silica fume, with paper pulp added at 0%, 3%, and 6%, and superplasticizer at 2%. The target strength for normal concrete is 25 MPa. The results show that using silica fume as a partial cement replacement can increase compressive strength by 3.36% and flexural strength by 7.24%. However, when silica fume is used with paper pulp, compressive and flexural strengths decrease. Adding both paper pulp and superplasticizer alongside silica fume results in an increase in strength, though the improvement is not significant.